Подход к выбору оптимальной структуры отраслевой гидрометеорологической системы на основе нечетких критериев - Доронина, Ю. В.; Валентюк, М. Р. (Eastern-European Journal of Enterprise Technologies, 2009)
One of approaches to a choice of optimum structure of branch system for the designing, based on a method of expert estimations and the criteria described in the form of indistinct sets with division into groups is led